A Survey on Acquisition, Tracking, and Pointing Mechanisms for Mobile Free-Space Optical Communications - Kaymak, Yagiz; Rojas-Cessa, Roberto; Jianghua Feng; Ansari, Nirwan; MengChu Zhou; Tairan Zhang (IEEE Communications surveys and tutorials, 2018)
This paper presents a comprehensive survey on acquisition, tracking, and pointing (ATP) mechanisms used in free-space optical (FSO) communications systems. ATP mechanisms are a critical component for a wide variety of use cases of mobile FSO communications. ATP mechanisms are used to align an FSO transmitter and receiver to attain line-of-sight, which is required for effective operation of FSO communications. Transceiver motion is not only associated to mobile stations but also to temporary displacements experienced by stationary FSO terminals, such as in building-to-building FSO communications. This survey categorizes ATP mechanisms according to their working principles, use cases, and implementation technology. This paper also discusses advantages and disadvantages of the surveyed ATP mechanisms, and presents a discussion on challenges and future research.